A recurring packing contact in crystals of InlB pinpoints functional binding sites in the internalin domain and the B repeat. Issue 3 (21st February 2022) - Geerds, Christina; Bleymüller, Willem M.; Meyer, Timo; Widmann, Christiane; Niemann, Hartmut H.
Abstract : InlB, an invasion protein from the facultative intracellular pathogen Listeria monocytogenes, is a multi‐domain protein that binds and activates the human receptor tyrosine kinase MET. Three new InlB crystal structures reveal the relative orientation of the first two domains (the internalin domain and the B repeat) for the first time. A recurrent packing contact formed by all five crystallographically independent molecules highlights functionally important binding sites in the internalin domain and the B repeat. Abstract : InlB, a bacterial agonist of the human receptor tyrosine kinase MET, consists of an N‐terminal internalin domain, a central B repeat and three C‐terminal GW domains. In all previous structures of full‐length InlB or an InlB construct lacking the GW domains (InlB392 ), there was no interpretable electron density for the B repeat. Here, three InlB392 crystal structures in which the B repeat is resolved are described. These are the first structures to reveal the relative orientation of the internalin domain and the B repeat. A wild‐type structure and two structures of the T332E variant together contain five crystallographically independent molecules. Surprisingly, the threonine‐to‐glutamate substitution in the B repeat substantially improved the crystallization propensity and crystal quality of the T332E variant. The internalin domain and B repeat are quite rigid internally, but are flexibly linked to each other. The new structures show that inter‐domain flexibility is the most likely cause of the missing electron density for the B repeat in previous InlB structures. A potential binding groove between B‐repeat strand β2 and an adjacent loop forms an important crystal contact in all five crystallographically independent chains. This region may represent a hydrophobic `sticky patch' that supports protein–protein interactions. This assumption agrees with the previous finding that all known inactivating point mutations in the B repeat lie within strand β2. The groove formed by strand β2 and the adjacent loop may thus represent a functionally important protein–protein interaction site in the B repeat.